FRI0560 Argentinian register of biologics treatments (biobadasar). results. (23rd January 2014) - Saurit, V.; De La Vega, M. C.; Citera, G.; Catay, E.; Quinteros, A.; Rillo, O.; Gomez, G.; Gobbi, C.; Capuccio, A.; Exeni, I.; Eimon, A.; Mussano, E.; et al.
Abstract : Background: It´s known that LatinAmerican countries have different prevalence of infectious diseases and so it´s important to assess the incidence of adverse events using biologics to compare in the future with results from other registries Objectives: The objective is to communicate data from BIOBADASAR, Argentine Registry of Adverse Events (AE) caused by the use of biological agents in Rheumatology Methods: All Patients with rheumatic diseases that requires biologic treatment and a control patient, not treated with biological agents, were included in the database from 31 sites participating along Argentine. Three data areas were studied: patient features, treatment assigned and adverse events(AE). The BIOBADASER database was given from the Spanish Society of Rheumatology for our use. Loading data began in August 2010 and closed for this analysis, in July 2012. The Infostat software was used to stadistic analysis. Incident rates, relative risk and person/year incidence for adverse events were calculated Results: 1508 patients were incorporated with 1909 treatments. 1197 women (79%) and 311 men(21%). The mean age was 55 years (range 3 to 90). 1107 patients (58%) were treated with biologic agents (cases) and 802 (42%) were controls. 1199 patients had rheumatoid arthritis (80%) and 137 psoriatic arthritis (9%) among the main diagnoses. The median time of progression of disease was 9 years. The most frequent biologic used was etanercept (50%of treatments) with a survival to treatment in months of 28 followed by adalimumab with 22.7%of the treatments and a survival in months of 26. The most frequent cause of treatment interruption for the cases was AE (41%) followed by inefficacy (33%). The incidence of serious adverse events was 28/1000ptesyears in the biologic group vs 3/1000 patient year in the control group (RR 6.8;CI 4.1-11.2;p<0, 05). The most common AE was infection with a RR 5.49 (CI 4, 1-7.1;p<0, 05). Within infections pneumonia had a RR of 30 (CI 7.1-14.9; p<0, 05 ), herpes zoster RR 5.29 (CI 1.7-16; p<0, 05) and cellulitis with a RR 5.5 (CI 1, 5-19, 8 p<0, 05). Tumoral diseases had a RR 3.32 (CI 1.5-7.0; p<0, 05). There was 3 cases of Tuberculosis in the biological group and 1 in the control group (non significant difference) Conclusions: This is the BIOBADASAR report showing the reality of biological treatments in Argentina. The patients of LatinAmerican countries could show some differences with other countries using the same treatments due to differences in regional diseases, vaccination or tolerability to pathogen agents Acknowledgements: María Laura Kozono. Monitora Sociedad Argentina de Reumatología Disclosure of Interest: None Declared